Implementation of the Mamdani Fuzzy Method to Evaluate the Performance of Lecturers in the Research Field - Alwendi Alwendi; Khairunnisa Samosir; Mingliang Suo; Yang Fan (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2022)
Today, information technology, especially soft computing technology, has grown very rapidly. One of the soft computing technologies that has been widely developed is fuzzy logic, because it can be used to measure various phenomena that are ambiguous, disguised or fuzzy. One of the research topics that uses the application of fuzzy logic is the assessment system in the field of research. Research by Lecturers at the University of Graha Nusantara Padangsidimpuan in Simlitabmas Data Still in the Guidance Category to upgrade to the Middle Category UGN Padangsidimpuan lecturers are challenged to be able to develop, devote, and apply the knowledge needed in research. For that we need an application that can be used to calculate and record the performance of Lecturers on the resulting Research. The purpose of this study is to apply fuzzy logic with the Mamdani method in assessing the research performance of lecturers at the University of Graha Nusantara Padangsidimpuan. This research uses Mamdani Fuzzy Logic. Fuzzy Mamdani method is a way to map an input space into an output space. This method is a mathematical framework used to represent uncertainty, ambiguity, imprecision, lack of information, and partial truth. The stages of research using the Mamdani method are Creating Input Variables taken from Sinta-accredited Articles, Simlitabmas Grant Articles and Articles in International and National Journals. Finding the Max-Min Value of Each Variable. Creating a fuzzy set using the Mamdani method. Creating Assertions with Defuzzification using Matlab.